Way toward ``dietary pesticides'': molecular investigation of insecticidal action of caffeic acid against helicoverpa armigera - Joshi, Rakesh S.; Wagh, T. P.; Sharma, N.; Mulani, Fayaj A.; Sonavane, U.; Thulasiram, H. V.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Agricultural and Food Chemistry, 2014)
Bioprospecting of natural molecules is essential to overcome serious environmental issues and pesticide resistance in insects. Here we are reporting insights into insecticidal activity of a plant natural phenol. In silico and in vitro screening of multiple molecules supported by in vivo validations suggested that caffeic acid (CA) is a potent inhibitor of Helicoverpa armigera gut proteases. Protease activity and gene expression were altered in CA-fed larvae. The structure-activity relationship of CA highlighted that all the functional groups are crucial for inhibition of protease activity. Biophysical studies and molecular dynamic simulations revealed that sequential binding of multiple CA molecules induces conformational changes in the protease(s) and thus lead to a significant decline in their activity. CA treatment significantly inhibits the insect's detoxification enzymes, thus intensifying the insecticidal effect. Our findings suggest that CA can be implicated as a potent insecticidal molecule and explored for the development of effective dietary pesticides.
Keywords: Caffeic acid; Helicoverpa armigera; insecticidal activity; protease inhibitor

Efficient trifluoromethylation of C(sp(2))-H functionalized alpha-oxoketene dithioacetals: a route to the regioselective synthesis of functionalized trifluoromethylated pyrazoles - Sharma, N.; Kumari, N.; Chundawat, T. S.; Kumar, S.; Bhagat, S. (RSC Advances, 2017)
An operationally simple approach for the regioselective construction of diversely substituted trifluoromethylated pyrazoles via nucleophilic trifluoromethylation of iodo-substituted alpha-oxoketene dithioacetals is described. X-ray crystallographic studies confirmed the trifluoromethylation as well as formation of a regioselective cyclized product. Furthermore, trifluoromethylated pyrazoles bearing thiomethyl groups may allow further functionalization and are of considerable interest in medicinal chemistry.

Facile synthesis of β-functionalized “push-pull” Zn(II) porphyrins for DSSC applications - Prakash, K. (Dyes and Pigments, 2017)
Three new β-substituted “push-pull” Zn(II) porphyrin dyes with various electron donors at meso-positions and cyanoacetic acid as acceptor at β-position have been designed and synthesized. These porphyrins have been characterized by UV-Vis, Fluorescence, 1H NMR and 13C NMR spectroscopic techniques and cyclic voltammetric studies. The Soret and Q band of Zn(II) porphyrin dyes were found to be red-shifted (30–35 nm) as compared to ZnTPP. The fluorescence quenching and the decrement in quantum yield and lifetime suggest intramolecular charge transfer from donor to acceptor. Zn porphyrins exhibited anodic shift in their first redox potentials (0.03–0.11 V) as compared to ZnTPP. The HOMO-LUMO energy levels of Zn porphyrin dyes were compared with the conduction band of TiO2 and the electrolyte I−/I3 −. The HOMO levels of all the dyes are sufficiently higher than the energy level of electrolyte I−/I3 − and LUMO levels significantly lower than the conduction band of TiO2 which reflect the feasibility of facile electron-transfer. ZnT(Mes)P(CN-COOH) has been co-sensitized with N719 dye to further improve the PCE efficiency. These dyes displayed power conversion efficiency (PCE) of η = 1.72–3.13% where co-sensitized ZnT(Mes)P(CN-COOH) (N719) dye demonstrated maximum PCE efficiency up to 5.35%, with a Jsc of 11.8 mA cm−2, a Voc of 630 mV and a fill factor (FF) of 72% due to better light harvesting capacity.
Keywords: charge transfer; Conduction Bands; Cyanoacetic Acid; Electrolytes; Floorescence; Redox Reaction; zinc compounds